ANALISIS PERILAKU AGRESIF SISWA DITINJAU DARI ASPEK TINGKAT PENDIDIKAN, EKONOMI, PEKERJAAN ORANG TUA SISWA DISMPN 4 PEKANBARU - Santi, Welly Grafi; ', Rosmawati; Saam, Zulfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: At school, most teens showed a negative behavior, one of which is aggressive behavior, which is an act of deliberate on other people, causing physical and psychological pain on other people. While the things that affect aggressive behavior can come from parents, among others, the level of education, the economy and the job of parents. The objectives of this research are: 1) to obtain an image of aggressive behavior of students in terms of parental education level, 2) to obtain an image of aggressive behavior of students in terms of parent economy, and 3) to obtain a picture of aggressive behavior of students in terms of parent work. The population of this study is all students of class VIII in SMPN 4 Pekanbaru consisting of 10 classes. A sample of 144 students. This research is a quantitative study with descriptive approach surve. Instrument data collection using a questionnaire which is then analyzed by grouping data and calculating the percentage. the results of this research are: 1) The dominant student behavior is very aggressive of his parents with high education (7.6%). The student's aggressive behavior is highly educated (64.6%). While the behavior of students who are not aggressive parents are highly educated (0.7%). 2) dominant student behavior is very aggressive parent at middle economic level equal to (6.2%). The aggressive student behavior of his parents is at the middle economic level of (39.6%). While the student's non-aggressive behavior is at the middle economic level of (0.7%). 3). The dominant student behavior is very aggressive his parents work as private employees (6.9%). Then the aggressive student behavior of his parents worked as civil servants (18.1%). While the behavior of students who are not aggressive have parents who work as entrepreneurs (11.8%).Keywords : Aggressive behavior, educational level, economy, work